Long-term Patterns of Patient Portal Use for Pediatric Patients at an Academic Medical Center - Steitz, Bryan D.; Cronin, Robert M.; Davis, Sharon E.; Yan, Ellen; Jackson, Gretchen P. (Applied Clinical Informatics, 2017)
Background: Patient portal adoption has increased over the last two decades. Most research about patient portals has focused on adult populations in the primary care and medical specialty settings.Objective: We describe initial and long-term portal use by pediatric patients and their caregivers in a broadly deployed patient portal at an academic medical center.Methods: We analyzed portal usage for pediatric patients and their caregivers from 2008 to 2014. We recorded usage events with time stamps; user role defined as self, surrogate (i.e., parent or guardian), or delegate; and functions accessed. Usage events were grouped into sessions to calculate descriptive statistics by patient age, user role, and active use over time.Results: From 2008 to 2014, the number of portal accounts increased from 633 to 17,128. 15.9% of pediatric patients had their own account; 93.6%, a surrogate account; and 2.2% a delegate account. During the study period, 15,711 unique users initiated 493,753 sessions and accessed 1,491,237 functions. Most commonly used functions were secure messaging (accessed in 309,204 sessions; 62.6%); test results (174,239; 35.3%) and appointments (104,830; 21.2%). Function usage was greatest for patients ages 0-2 years (136,245 functions accessed; 23.1%) and 15-17 years (109,241;18.5%). Surrogate users conducted 83.2% of logins for adolescent patients. Portal accounts were actively used for < 1 year for 9,551 patients (55.8%), 1-2 years for 2,826 patients (16.5%), 2–3 years for 1,968 patients (11.5%) and over 3 years for 2,783 patients (16.3%).Conclusion: Pediatric patients and caregivers have avidly used messaging, test result, and appointment functions. The majority of access was done by surrogates. Adolescent portal usage increased with age. Most accounts for pediatric patients were only used actively for a few years, with peak usage for patients in early childhood and late adolescence.Citation: Steitz BD, Cronin RM, Davis SE, Yan Z, Jackson GP. Long-term Patterns of Patient Portal Use for Pediatric Patients at an Academic Medical Center. Appl Clin Inform 2017; 8: 779–793 https://doi.org/10.4338/ACI-2017-01-RA-0005
Keywords: Patient portal; Patient engagement; Consumer health informatics; Pediatrics; Electronic health records and systems; Internet Portal